Nietzsche in the nineteenth century : social questions and philosophical interventions - Holub, Robert C. (Intellectual history of the modern age., 2018)
Nietzsche in the Nineteenth Century shows how Nietzsche formulated his thought in an ongoing dialogue with the concerns of his contemporaries and how his philosophy can be conceived as a contribution to the debates taking place in Europe at the time in the realms of politics, society, and science.